Critical switching fluence of L10-FePt nanoparticles with practical size to ultrafast all-optical polarization switching. (1st September 2017) - Huang, Tao; Wang, Haiwei; Cheng, Weiming; Zou, Yuhao; Xie, Changsheng
Abstract: The magnetic storage industry will be pushed into a new era by emerging magnetic materials and ingenious read/write techniques. Recently, L10 -FePt nanoparticles with exceptionally high uniaxial anisotropy, combined with the technique of all-optical magnetic switching, have increasingly drawn the attention of researchers. Focusing on L10 -FePt nanoparticles, we report the superparamagnetic size limits and three elaborate stages of magnetic orientation switching, which demonstrate that in terms of the opto-magnetic responses of L10 -FePt nanoparticles with the size of 6 nm, the fluence of an ultrashort laser pulse should not be larger than the level of 40 mJ/cm 2 in order to achieve the helicity-dependent all-optical switching.